Surface Water Quality Modelling - Lindenschmidt, Karl-Erich (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue showcases some advanced methodologies used in surface water quality modelling. Its aim is to introduce several topics that are new in the field of surface water quality modelling and help spur new developments in each of the topics. It is intended for a readership consisting of researchers, academicians, consultants and government agency representatives. The editor of this Special Issue wishes to thank all authors, reviewers and academic editors in their contributions, without whom the publishing of this collective work would not have come to pass.